2017
DOI: 10.1080/09593330.2017.1418913
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide-assisted photocatalytic degradation of textile wastewater using titanium dioxide and zinc oxide

Abstract: The present work investigated the degradation of a dyeing factory effluent by advanced oxidative process under UV irradiation. TiO and ZnO were used as catalysts and the influence of different concentrations of HO added to the system was studied. The catalysts were characterized in terms of crystal structure (X-ray diffraction), textural properties (Brunauer-Emmett-Teller area and pore volume) and point of zero charge, which indicated the semiconductors had a positively charged surface in an acidic medium. Aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Furthermore, it can also be added to the reaction medium during photocatalytic treatment to improve the efficiency of the process through the production of additional radical species. For example, Domingues et al [63] investigated the hydrogen peroxide-assisted photocatalytic degradation of a dyeing factory effluent using TiO 2 or ZnO as catalysts. The authors found that the addition of hydrogen peroxide at a concentration of 10 −2 M to the effluent significantly increased the removal of dyes without generating secondary pollutants.…”
Section: Effect Of Hydrogen Peroxidementioning
confidence: 99%
“…Furthermore, it can also be added to the reaction medium during photocatalytic treatment to improve the efficiency of the process through the production of additional radical species. For example, Domingues et al [63] investigated the hydrogen peroxide-assisted photocatalytic degradation of a dyeing factory effluent using TiO 2 or ZnO as catalysts. The authors found that the addition of hydrogen peroxide at a concentration of 10 −2 M to the effluent significantly increased the removal of dyes without generating secondary pollutants.…”
Section: Effect Of Hydrogen Peroxidementioning
confidence: 99%
“…Furthermore, ZnO Ps have been applied to textile fibers to improve flame retardancy and thermal stability and to achieve moisture management and thermal insulation, electrical conductivity, and hydrophobicity [5][6][7][8][9][10][11][12][13][14][15][16]. The photocatalytic properties also enable ZnO Ps to be used as degradation agents for different pollutants, such as dyes and surfactants present in textile industry wastewaters [12,[17][18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Em geral, percebeu-se que as características mais monitoradas para efluentes têxteis são DQO, DBO, pH, turbidez, cor aparente e sólidos totais (ST). A determinação de carbono orgânico total, análise essa dependente de um equipamento mais complexo em laboratórios, foi encontrada somente em sete dos 48 trabalhos consultados, 8,9,11,26,39,41,50 enquanto a DQO foi quantificada por praticamente todos, por ser uma análise de menor custo. Tanto os valores de DQO, quanto os de DBO são exigidos por órgãos ambientais.…”
Section: Características De Efluentes Têxteis Brasileirosunclassified